2022
DOI: 10.29312/remexca.v13i2.2866
|View full text |Cite
|
Sign up to set email alerts
|

Las abejas sin aguijón (Tribu Meliponini) en los agroecosistemas de América Latina

Abstract: Los meliponinos son importantes polinizadores de plantas silvestres y cultivadas en América Latina. Además, estas abejas tienen características de un bioindicador, información necesaria para desarrollar estrategias de conservación y manejo sostenible para las especies de importancia cultural, ecológica y económica. El objetivo de este trabajo es determinar las especies de meliponinos que polinizan los agroecosistemas en América Latina y su uso como bioindicadores, lo cual servirá para implementar estrategias e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 68 publications
0
3
0
5
Order By: Relevance
“…We found that the most frequent floral visitors to coffee were A. mellifera and three stingless bees T. angustula , S. mexicana and P. bilineata . Previous studies have pointed out that stingless bees might be playing a potential role as coffee pollinators in our region, as suggested by a review of 46 crops in Latin America (review in Real‐Luna et al 2022). It has also been observed that A. mellifera is an important pollinator on coffee crops (Manrique & Thimann 2002; Raw & Free 1977; Roubik 2002).…”
Section: Discussionmentioning
confidence: 63%
“…We found that the most frequent floral visitors to coffee were A. mellifera and three stingless bees T. angustula , S. mexicana and P. bilineata . Previous studies have pointed out that stingless bees might be playing a potential role as coffee pollinators in our region, as suggested by a review of 46 crops in Latin America (review in Real‐Luna et al 2022). It has also been observed that A. mellifera is an important pollinator on coffee crops (Manrique & Thimann 2002; Raw & Free 1977; Roubik 2002).…”
Section: Discussionmentioning
confidence: 63%
“…Las abejas sin aguijón es uno de los grupos más abundantes del Neotrópico que se caracterizan por ser polinizadores de los diferentes ecosistemas (Rasmussen, 2004) y se las usa como bioindicadores que permite implementar estrategias de conservación y manejo sostenible para las especies de importancia cultural, ecológica y económica (Real-Luna et al, 2022). Además dentro de su biología y las formas de vida de las abejas se basa en tres estrategias como: anidación, reproducción y comportamiento: social, solitaria y cleptoparásita.…”
Section: Beneficios De La Meliponiculturaunclassified
“…The Meliponini or stingless bee tribe of the Apoidea, is distributed in the tropical and subtropical regions of Africa, Asia, Australia and America (Crane, 1992). The 550 described species (58 genera) of meliponines pollinate the native flora and agroecosystems of these regions with which they have evolved (Grüter, 2020;Real-Luna et al, 2022).…”
Section: Introductionmentioning
confidence: 99%